1986
DOI: 10.1136/adc.61.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral haemorrhage after the neonatal period.

Abstract: SUMMARY Intracerebral haemorrhage is rare in childhood. We have reviewed the last 10 years' experience, in our referral area, of parenchymatous intracerebral haemorrhage in children from 1 month to 16 years of age. There were 27 cases, five of which were intracerebellar and two predominantly intraventricular. The commonest aetiology was vascular malformation (10), followed by haemorrhage into tumour (four), and coagulopathies (five).Clinical features were non-specific, but altered consciousness, headache, vomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Most HS in children are supratentorial, and the basal ganglia are rarely involved. Three large series of children with HS revealed that over 80% of the hemorrhages were in the cortical region and less than 10% involved the basal ganglia [5,66,67].…”
Section: Epidemiologymentioning
confidence: 99%
“…Most HS in children are supratentorial, and the basal ganglia are rarely involved. Three large series of children with HS revealed that over 80% of the hemorrhages were in the cortical region and less than 10% involved the basal ganglia [5,66,67].…”
Section: Epidemiologymentioning
confidence: 99%
“…No child in this study cohort had ICH related to hypertension although other studies have reported hypertension as a risk factor in <5% of children with ICH. 21,22 …”
Section: Commentmentioning
confidence: 99%
“…Improvements in pediatric critical care and neurosurgical techniques may account from some of this reduction in mortality [7,72]. Pooled data from multiple, somewhat heterogeneous studies suggest an average mortality of 25% in children with HS [6], although individual study estimates range from 7% [73] to 54% [22].…”
Section: Neurologic Outcome and Hs Recurrencementioning
confidence: 99%
“…Hematologic abnormalities are reported to be the major risk factor in 10 to 30% of HS in most series [5,12,15,22]. Hematologic causes of IPH include thrombocytopenia and hemophilia, and coagulopathies.…”
Section: Risk Factors For Hs In Childhoodmentioning
confidence: 99%